Dynamic impacts of urbanization development on carbon storage and NPP: spatiotemporal responses in the Wanjiang urban belt (2000–2020) - Fang, Jiawei; Tang, Huan; Yuan, Jing (Frontiers in Environmental Science, 2026)
IntroductionUrban agglomerations, as pivotal spatial units in global urbanization processes, are central to urban science, their land use/cover changes directly regulate regional carbon cycles and profoundly affect ecosystem carbon storage and net primary productivity (NPP). To clarify the dynamic changes, driving factors, and future trends of these two key ecological indicators in Wanjiang Urban Agglomeration, multiple models and analytical methods were integrated.MethodsThe Carbon Storage module of the InVEST model was used to assess regional carbon stocks, while the improved CASA model quantified multi-period NPP using remote sensing and climate data. A random forest algorithm combined with the SHAP method analyzed the independent effects of topographic, anthropogenic, and natural factors, and the PLUS model combined with Markov Chain forecast 2040 carbon storage.ResultResults show urban area expanded by 2,230.87 km2 (3.57% annual growth), primarily from cultivated land (4.52 × 10 km2 to 4.26 × 10 km2). Annual carbon storage loss reached 0.25 × 10 tC and NPP loss 17.49 × 104 tC, with both first rising then falling. Carbon storage is predominantly driven by topographic factors (with thresholds) and secondarily by natural factors, while NPP is jointly regulated by topographic and climatic drivers. Anthropogenic factors exert the weakest influence on both. The 2040 forecast indicates continued carbon storage decline.DiscussionThis work clarifies key dynamic patterns and driving mechanisms, providing scientific support for regional ecological protection and advancement of “carbon peaking and carbon neutrality” goals.